Pengaruh Kompetensi Digital Dan Customer Relationship Management Terhadap Peningkatan Omzet Usaha Dengan Inovasi Produk Sebagai Variabel Moderasi Pada Umkm Di Kabupaten Pasuruan - Khoirul Anwar anwar; Khamdan Suriyok; M. Mashudi Azrullah1 (Institut Teknologi dan Bisnis Yadika, 2026)
The rapid development of digital technology and increasing business competition require Micro, Small, and Medium Enterprises (MSMEs) to enhance their ability to utilize technology and build strong relationships with customers in order to improve business performance. Digital competence and Customer Relationship Management (CRM) are important factors that can support the increase of business turnover. This study aims to analyze the effect of digital competence and Customer Relationship Management (CRM) on business turnover growth, with product innovation serving as a moderating variable. This study employed a quantitative research approach using a survey method. The sampling technique used was purposive sampling targeting MSME owners. Data analysis was conducted using Moderated Regression Analysis (MRA) with the assistance of SPSS software. The results indicate that digital competence has a positive and significant effect on business turnover growth. Customer Relationship Management (CRM) also has a positive and significant effect on business turnover growth. Furthermore, product innovation is proven to moderate and strengthen the relationship between digital competence and business turnover growth, while also having a direct significant effect on business turnover growth; therefore, it is categorized as a quasi moderator. However, product innovation is unable to moderate the relationship between Customer Relationship Management (CRM) and business turnover growth, although it still has a direct significant effect on business turnover growth and is therefore categorized as a predictor moderator.